Mobile Telephony as an ICT Tool for Agricultural Information Dissemination in Developing Countries: A Review - Byamukama, Willbroad; Businge, Phelix Mbabazi; Kalibwani, Rebecca (East African Journal of Agriculture and Biotechnology, 2023)
In emerging nations, the use of information and communication technology has considerably benefitted the advancement of agriculture, health, rural development, and education. This technique has had a considerable impact onthe way agriculture is developed in third-world countries. For information on the weather and prices, farmers now have direct access to the market, buyers, customers, and the metrological department. Information and communication technology has increased farmer incomes all over the world. It is now vital to provide access to facilities and introduce technology to rural areas where farmers lack knowledge, information, and skills regarding this technology. Several studies have also demonstrated that the adoption of information and communication technology tools in agricultural production has increased agricultural productivity. A few of the major problems and challenges that farmers encounter includes inadequate information transfer, poor agricultural practices, record reconciliation between farmers, the government, and traders, and a lack of understanding of the best farming techniques.
Keywords: Developing Countries; Agricultural Marketing; ICT; Farmers